2019
DOI: 10.15252/msb.20188689
|View full text |Cite
|
Sign up to set email alerts
|

Defining the RNA interactome by total RNA ‐associated protein purification

Abstract: The RNA binding proteome ( RBP ome) was previously investigated using UV crosslinking and purification of poly(A)‐associated proteins. However, most cellular transcripts are not polyadenylated. We therefore developed total RNA ‐associated protein purification ( TRAPP ) based on 254 nm UV crosslinking and purification of all RNA –protein complexes using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 104 publications
8
139
1
Order By: Relevance
“…Specifically, there were 439 direct mRNA substrates of Pfk2 with 559 discrete binding sites, 1,001 mRNA substrates with 1,432 binding sites for Eno1, and 721 mRNA substrates with 1,014 binding sites for Fba1 ( Fig S1B, right panels). The results of Eno1 PAR-CLIP-seq were in agreement with a recent analysis of Eno1 in normoxic conditions by CRAC (a method that UV crosslinks and affinity purifies protein-RNA complexes under denaturing conditions (Shchepachev et al, 2019)), providing additional validation of our identified binding sites. We identified 69 out of the top 100 bound mRNAs in the CRAC dataset.…”
Section: Glycolysis Enzymes Bind Similar Transcriptssupporting
confidence: 89%
“…Specifically, there were 439 direct mRNA substrates of Pfk2 with 559 discrete binding sites, 1,001 mRNA substrates with 1,432 binding sites for Eno1, and 721 mRNA substrates with 1,014 binding sites for Fba1 ( Fig S1B, right panels). The results of Eno1 PAR-CLIP-seq were in agreement with a recent analysis of Eno1 in normoxic conditions by CRAC (a method that UV crosslinks and affinity purifies protein-RNA complexes under denaturing conditions (Shchepachev et al, 2019)), providing additional validation of our identified binding sites. We identified 69 out of the top 100 bound mRNAs in the CRAC dataset.…”
Section: Glycolysis Enzymes Bind Similar Transcriptssupporting
confidence: 89%
“…In earlier work, we and others found that a surprisingly large number of enzymes of intermediary metabolism bind to RNA in vivo, among them the majority of enzymes in glycolysis [28,37]. For enolase (ENO-1), theses findings were confirmed and target RNAs were identified recently [38]. Here, we show that using PTex, it is likewise possible to extract RNA-binding enzymes such as ENO-1 (Fig.…”
Section: Ptex Step-by-stepsupporting
confidence: 79%
“…Along the same lines: the landscape of bacterial RBPs has not been determined at the same depth as for eukaryotic species; a major issue being the lack of poly(A) RNA necessary for interactome capture [5]. PTex allowed us for the first time to unbiasedly screen for proteins cross-linked to RNA in Salmonella Typhimurium [12] while RBPs in E. coli were purified by OOPS [40] and TRAPP [38].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that since coming across this paper, alternative variants of this method have been published (35). It turns out that three of these groups (1, 3, 4) were independently working on the same idea and coordinated efforts to simultaneously submit to bioRxiv.…”
Section: Commentarymentioning
confidence: 99%